Analisis Dampak Proyek Penguatan Profil Pelajar Pancasila terhadap Kemampuan Berliterasi Siswa Sekolah Dasar - Nazella Sefty; Najwa Rifia; Ichsan Fauzi Rachman (Publikasi Inspirasi Indonesia, 2025)
The low literacy skills of primary school students in Indonesia are still a major challenge in education, as reflected in international surveys. One of the efforts made to address this issue is the implementation of the Pancasila Learner Profile Strengthening Project (P5) in the Merdeka Curriculum, which aims to build character while improving literacy through a project-based learning approach. This research uses a systematic literature review method by analyzing various sources such as journal articles, books, research reports, and official documents to analyze the impact of P5 implementation on strengthening primary school students' literacy. The results show that P5 can increase students' active engagement in reading, writing, and critical thinking by exploring issues relevant to daily life. However, the implementation of this program still faces obstacles such as teachers' lack of understanding of the P5 concept, limited learning media, and suboptimal time management. Therefore, continuous training for teachers and strengthening the culture of literacy in the school environment are needed so that P5 can make a real contribution to early literacy development. This study is expected to be a reflection and recommendation for policymakers and education practitioners to improve the quality of literacy at the primary school level.